2015
DOI: 10.3906/sag-1404-57
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant effects of lycopene in acute cholestasis

Abstract: IntroductionMany clinical conditions, including strictures of the bile duct, gallstone complications of pancreatitis, or biliary surgery, are cited among etiologies that lead to a decrease in biliary flow, causing cholestasis (1). Cholestasis leads to acute hepatic injury and results in progressive fibrosis (2). The production of free oxygen radicals has been suggested to play an important role in the pathogenesis of cholestasis. One of the significant endpoints leading to liver damage arising from cholestasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 43 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…It reduced NO and MDA levels and improved reduced enzymatic level (i.e., CAT, GSTs, GSH, and SOD) in the BDL rat. In addition, lycopene decreased DNA damage [71].…”
Section: Hepatoprotectivementioning
confidence: 90%
“…It reduced NO and MDA levels and improved reduced enzymatic level (i.e., CAT, GSTs, GSH, and SOD) in the BDL rat. In addition, lycopene decreased DNA damage [71].…”
Section: Hepatoprotectivementioning
confidence: 90%
“…In addition to CAT, which plays a vital role in decomposing H 2 O 2 into O 2 and H 2 O, GPx is a critical enzyme that catalyzes the reduction of H 2 O 2 (46,47). Increased GPx and SOD levels in liver tissue can decrease oxidative stress-mediated injury in cholestatic animal models (48,49). Our findings showed that OD therapy in BDL-induced cholestatic rats significantly promotes the functions of SOD and GPx in liver tissue.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, reversions of lycopene on liver fibrosis are further reported in rodent models of high-cholesterol/ HFD and HFD, respectively, which may be related to its antioxidant and anti-inflammatory effects, the increase of macrophage M2-dominant polarization, or the downregulation of FABP7 expression [276][277][278][279][280]. Lycopene also reverses BDL-induced rat liver injury by inhibiting oxidative stress and DNA damage [281].…”
Section: Lycopenementioning
confidence: 99%